2011
DOI: 10.1108/00251741111094473
|View full text |Cite
|
Sign up to set email alerts
|

Do downsizing decisions affect organisational knowledge and performance?

Abstract: Purpose - This study seeks to examine the impact of downsizing and restructuring decisions and processes on perceptions of organisational knowledge and effectiveness after downsizing and restructuring events in \u22successful\u22 and \u22unsuccessful\u22 organisations. Design/methodology/approach - The study proposes a conceptual framework hypothesising that the impact of decisions and processes on levels of organisational knowledge are key determinants of effectiveness in post-downsizing and restructuring org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…When defining the knowledge retention in the organization Sitlington and Marshall (2011) emphasize the constant necessity of the personnel training and the importance of tacitknowledge amongst the personnel. According this scientist, the constant training and improvement is needed so that each member of the organization would precisely knew the limits of his responsibility and duties.…”
Section: Baporikar 2014mentioning
confidence: 99%
See 1 more Smart Citation
“…When defining the knowledge retention in the organization Sitlington and Marshall (2011) emphasize the constant necessity of the personnel training and the importance of tacitknowledge amongst the personnel. According this scientist, the constant training and improvement is needed so that each member of the organization would precisely knew the limits of his responsibility and duties.…”
Section: Baporikar 2014mentioning
confidence: 99%
“…According this scientist, the constant training and improvement is needed so that each member of the organization would precisely knew the limits of his responsibility and duties. According to Sitlington and Marshall (2011) it provides the premises for the organisation to deal with the planned and unplanned personnel turnover problem easier, since if the one employee is replaced the employees who worked with him are aware of his duties and responsibility and make the integration of the latter easier.…”
Section: Baporikar 2014mentioning
confidence: 99%
“…Culture leads to improvement in individual skills and experience cumulating into organizational knowledge. Sitlington and Marshall (2011) examined the impact of decision on organizational knowledge with firm performance and found that organization restructure their culture and climate to maximize knowledge. Most previous studies have highlighted the importance of knowledge on organizational performance.…”
Section: Wwwccsenetorg/ibrmentioning
confidence: 99%
“…According to Gibrat's law, firm growth reflects random shocks (Goddard, McMillan and Wilson, 2006) and firm size and/or firm history do not determine how firms will grow or decline in the future. In a nutshell, Gibrat's law predicts that since firm growth does not depend 2 Such resources and capabilities include business models (Cavalcante, Kesting and Ulhoi, 2011), market orientation (Cambra-Fierro, Florin, Perez, and Whitelock, 2011), governance modes (Cantarello, Nosella, Petroni, and Venturini, 2011), management practices and organizational processes (Hotho and Champion, 2010), the dynamic capability of the firm (Goktan and Miles, 2011), the decision making process within the firm (van Riel, Semeijn, Hammedi, and Henseler, 2011), innovative orientation (Rowley, Baregheh and Sambrook, 2011), knowledge and experience of certain employees (Sommer and Haug, 2011), organizational knowledge and management skills (Sitlington and Marshall, 2011), efficient procedure within the firm (Wernerfelt, 1984), firm culture (Barney, 1986;Lee, Lim and Pathak, 2011;and Naranjo-Valencia, Jimenez-Jimenez and Sanz-Valle, 2011), human and social capital (Jansen, Curseu, Vermeulen, Geurts and Gibcus, 2013), social trust (Bergh, Thorgren and Wincent, 2011), and trade contracts (McKelvie and Wiklund, 2010;and Wernerfelt, 1984). 3 One recent way to explain randomness in the firm growth rate uses the Gambler's Ruin problem, as described in Coad, Frankish, Roberts, and Storey (2013).…”
Section: Introductionmentioning
confidence: 99%